2021
DOI: 10.1037/law0000260
|View full text |Cite
|
Sign up to set email alerts
|

What are judges’ views of risk assessments, and how do tools affect adolescent dispositions?

Abstract: This work was originally disseminated as the first author's Master's thesis, and select findings were presented at the 19th Annual Conference of the International Association of Forensic Mental Health Services, Montreal, Canada. This research was supported by grants from the Social Sciences and Humanities Research Council of Canada, the American Psychology-Law Society, and the International Association of Forensic Mental Health Services. We thank Jourdan Jackson for her assistance in coding the qualitative dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
(102 reference statements)
1
2
0
Order By: Relevance
“…This fits also the reasons suggested by other criminal justice actors for resisting the use of risk-assessment tools (e.g. rejecting such tools' one-size-fits-all approach) (Jonathan-Zamir et al, 2019;Jonnson and Viljoen, 2021;cf. Burkes et al, 2017).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This fits also the reasons suggested by other criminal justice actors for resisting the use of risk-assessment tools (e.g. rejecting such tools' one-size-fits-all approach) (Jonathan-Zamir et al, 2019;Jonnson and Viljoen, 2021;cf. Burkes et al, 2017).…”
Section: Discussionsupporting
confidence: 72%
“…Studies have confirmed that space too is subject to different interpretations by professionals through spatial work that connects actors and institutional discourses, influences formal and informal work interactions, fosters the development of trust and embodies power relations (Stephenson et al, 2020). Space can be marked physically or abstractly by means of discourses and can acquire symbolic and emotional value as a negotiated phenomenon (Lefebvre, 1991).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It should be stressed that while we can easily distinguish between diagnostic and statistical uses—because they are generally based on separate sciences and serve different application purposes—anecdotal evidence and field studies show that psychopathy assessments are commonly used for both purposes. For instance, once a person undergoes a PCL-R assessment, the outcome is interpreted by practitioners both as a diagnostic measure of psychopathy and as a statistical inference to predict relevant behaviors such as institutional misconduct, criminal recidivism, parole violation, and rehabilitation (e.g., Archer et al, 2006; DeMatteo et al, 2014; Hill & Demetrioff, 2019; Hurducas et al, 2014; Jonnson & Viljoen, 2021; Viljoen, McLachlan, et al, 2010). This sort of dual-type usage is also recommended by psychopathy assessment developers and researchers.…”
Section: The Forensic Use Of Psychopathy Assessmentsmentioning
confidence: 99%